The Motives of Sumedang Residents in Consuming Sumedang Ekspres as the Primary Mass Media - Farid, Miftah; Hidayat, Dadang Rahmat; Supriadi, Dandi (Jurnal Kajian Jurnalisme, 2022)
The purpose of this study was to determine and analyze the motives of Sumedang residents in consuming Sumedang Ekspres as their primary mass media. People in the Sumedang region, West Java, are significant to examine because of their unique characteristics in using mass media. They are among the few who still rely on print newspapers for news, especially Sumedang Ekspres, in the age of online media. That is the main reason for looking at their motivation in consuming this newspaper as their primary source of information. This study used quantitative research methods with explanatory case studies, using questionnaires as instruments for collecting data. Theoretically, the audience's needs would be satisfied if their motives in consuming media were met. As a result, certain media that can fulfill the needs will be considered effective outlets. This is a basic assumption of the Uses and Gratifications Theory, which is employed as a theoretical basis of this study. The sample in this study was 95 respondents, taken from residents of Sumedang who consume Sumedang Ekspres on regular basis. The results show that the informational motive, as well as social motive, were implemented moderately by the respondents in terms of consuming Sumedang Ekspres as the major media. It is recommended to conduct further research by looking at the impact of people's motives toward newspaper reading satisfaction.